Patterns of Thought - Sypniewski, Bernard; Frankel Sypniewski, M. (Respectus Philologicus, 2013)
We have no system from ancient China comparable to Aristotelian logic or any other such system developed in the ancient Mediterranean world, but it cannot be said that the Confucian-era texts do not show that their authors were concerned to make cogent arguments—if not “arguments” in the strictly Western logical sense. We explore a way that might have satisfied the goal of presenting reasoned cases by analyzing a sample from a text known as the Da Xue(the Way of Great Learning), one of the five Confucian Classics. The Confucian Classics, especially the Da Xue, were roughly contemporary with the origins of Greek logical thought. This being so, they offer good examples of sophisticated, well-thought-out philosophical texts which were not subjected to Greek logical processes. The reader should be cautioned that we are not saying that this or any other classical Chinese text is illogical; we describe what we mean when we say that these texts exhibit a non-logical reasoning system. We assume that the Chinese author did not mimic other texts or oral statements without considerable thought. The text, which shows no non-Chinese influence, is heavily patterned. We contend that the patterns in the text are more than literary devices, but demonstrate non-Western reasoning.